Salagean-Type Harmonic Multivalent Functions Defined by Q-Difference Operator - Ahuja, Om P.; ÇETİNKAYA, ASENA; Mert, Oya (Univ Babes-Bolyai, 2022)
We introduce a new subclass of Salagean-type harmonic multivalent functions by using q-difference operator. We investigate sufficient coefficient es-timates, distortion bounds, extreme points, convolution properties and neighbor-hood for the functions belonging to this function class.
Keywords: Q−calculus; Q−difference Operator; Sălăgean Differential Operator; Multivalent Function.